METHODOLOGICAL BASIS OF SOCIAL PEDAGOGICAL AND SOCIO-PEDAGOGICAL ACTIVITY DEVELOPMENT (American Journal of Interdisciplinary Research and Development, 2023)
This article provides an understanding of the criteria, principles, and methods of pedagogy and social pedagogy, in which children are responsible for their behavior as a member of the future society; caring, volunteering work, the ability to find will power in difficult circumstances, overcome difficulties, hardworking, endless love for motherland, humility, gratitude and other qualities are highlighted.